PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2010-2019 - Rini Aisyah; Rosalia Nansih Widhiastuti (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2021)
This study aims to determine the effect of financial ratios on profit growth in food and beverage industry companies listed on the IDX in the 2010-2019 period. The population in this study are all companies listed on the IDX for the 2010-2019 period with a total of 33 companies. The sample used in this study were 12 companies in accordance with the sampling criteria. The analysis method used is panel data regression analysis. The results of this study indicate that simultaneously Current Ratio (CR), Total Asset Turnover (TATO), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER) and Net Profit Margin (NPM) affect profit growth in industrial companies, food and beverages listed on the IDX for the 2010-2019 period. Partially, the Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) variables have a positive and significant effect on profit growth in food and beverage industry companies listed on the IDX for the 2010-2019 period, while Current Ratio (CR), Debt to Asset Ratio (DAR) and Net Profit Margin (NPM) have a negative and significant effect on profit growth in food and beverage industry companies listed on the IDX for the 2010-2019 period.